A lamprey neural cell type atlas illuminates the origins of the vertebrate brain - Lamanna, Francesco; Hervas Sotomayor, Francisca; Oel, A. Phillip; Jandzik, David; Sobrido-Cameán, Daniel; Santos-Durán, Gabriel N.; Martik, Megan L.; Stundl, Jan; Green, Stephen A.; Brüning, Thoomke; Mößinger, Katharina; Schmidt, Julia; et al. (Nature ecology & evolution, 2023)
The vertebrate brain emerged more than ~500 million years ago in common evolutionary ancestors. To systematically trace its cellular and molecular origins, we established a spatially resolved cell type atlas of the entire brain of the sea lamprey—a jawless species whose phylogenetic position affords the reconstruction of ancestral vertebrate traits—based on extensive single-cell RNA-seq and in situ sequencing data. Comparisons of this atlas to neural data from the mouse and other jawed vertebrates unveiled various shared features that enabled the reconstruction of cell types, tissue structures and gene expression programs of the ancestral vertebrate brain. However, our analyses also revealed key tissues and cell types that arose later in evolution. For example, the ancestral brain was probably devoid of cerebellar cell types and oligodendrocytes (myelinating cells); our data suggest that the latter emerged from astrocyte-like evolutionary precursors in the jawed vertebrate lineage. Altogether, our work illuminates the cellular and molecular architecture of the ancestral vertebrate brain and provides a foundation for exploring its diversification during evolution.